Mixing Codes in Comments on Youtube Video Posts Debate for Presidential and Vice Presidential Candidates for the 2024 Election - Dwi Nurhidayah; Putri Widianingsih; Jaja; Masrurih (International Journal of Educational Research Excellence (IJERE), 2024)
This February, Indonesia will hold a democratic party to elect members of parliament and the president. Of course, the political and national atmosphere became warm with various political ripples and upheavals occurring, including political campaign activities, both political party campaigns and campaigns for Presidential and Vice Presidential Candidates. Various attributes and activities of political campaign speeches are interesting to study from various aspects, including the aspect of language use. This research aims to identify forms of code mixing found in KompasTV YouTube comments. This research method uses a descriptive method with a qualitative approach. The data for this research are comments from internet users (netizens) that researchers observed through screenshots from the comments column on the KompasTV YouTube channel. The data comes from the comments column of the KompasTV YouTube channel which contains elements of code mixing. Data collection techniques use listening, note-taking and documentation techniques. Data were analyzed using the Mills and Huberman model through the stages of data identification, data reduction, data analysis, and data presentation. Based on the research results, it was concluded that the code mixing that many netizens do in the comments column occurs at the word level. This is very possible because comments in word form are simpler, more practical and "to the point".